SUPERVISI MANAJERIAL PROFESI KEGURUAN DALAM JABATAN - Musdalifah, Musdalifah (Idaarah: Jurnal Manajemen Pendidikan, 2020)
Supervision as a part of management education is often assumed to be an inspection, reprimanding, and patronizing teachers. Professional supervision will lead teachers to become professional teachers. Professional teachers are expected to realize the goal of Indonesian people as can be seen in educational regulation of Indonesia. There are two problems in this paper, namely: 1) What is meant by the managerial supervision of the teaching profession in the office? 2) Why do teachers need managerial supervision? Managerial supervision places more emphasis on supervision to improve school administration. Managerial supervision of teacers office is supervision controling by school supervisor to teachers to arrange their duties. Managerial supervision is needed to reach the goals, objectives and supervision techniques as well as the steps that need attention from the supervisor.